Studi Kualitas Fisik Kimia Sumur Gali Dusun Lassang-Lassang Desa Arungkeke Kec. Arungkeke Kab. Jeneponto - Sitti Raodhah; Andi Susilawaty; Muhammad Syamsul Bachri (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2015)
Groundwater contamination can cause serious problems, since groundwater is a source of wa-ter that is used by most of the population to meet the drinking water needs. Discuss the specific wa-ter chemistry requirements, so it is important because many chemical content of water which cause bad effect on health because it is not in accordance with the biochemical processes of the body. This study aims to determine the physical and chemical quality of water dug wells located in the hamlet village Lassang-Lassang Arungkeke Arungkeke Jeneponto the District in 2014, with a descriptive ap-proach. The study used purposive sampling method, with the criteria that health complaints observa-tion using a questionnaire, and the Field Test Laboratory tests to show the water content of dug wells. The survey results revealed that for the physical parameters of the existing color proofing 4 (40.0%) samples of well water were eligible and 6 (60.0%) were not eligible, for examination of the smell, there are 9 (90.0%) were qualified and 1 (10.0%) were not eligible, and for examination taste 4 (40.0%) were eligible and 6 (60.0%) are not eligible. Dug well water quality of the chemical parame-ters of Iron (Fe) all (100.0%) did not qualify that exceeds the maximum allowable limit of 1.0 mg / L. and Manganese (Mn) (100%) were allowed to meet the requirements of 0.5 mg / L, while the use of health complaints dug well water contained 31 (57.4%) who experienced health complaints and 24 (42.6%) were not experiencing health complaints. To maintain water quality dug well, the public can expect to pay more attention and get used to the cooking water to a boil.Keywords : dug wells, Manganese (Mn), Iron (Fe), color, smell and Taste.